Fast Digital Promotion Dalam Meningkatkan Penjualan Home Production Pada Masyarakat Padukuhan Santren Sleman - Sutiyono; Nasrulloh, Rifqi Syarif; Zahro, Alfinatuz; Agustiani, Dwi Irma (Rahmatan Lil 'Alamin Journal of Community Services, 2023)
The "Tuwuh Makmur" Farmer's Group, Padukuhan Santren, Caturtunggal Village is a forum for women farmers' associations that have an empowerment and profit-oriented orientation in the economic sector in order to achieve a better standard of living. Based on the results of observations and FGDs conducted with women who are members of KWT Tuwuh Makmur, there are still several obstacles in promoting digital-based products and low skills in the fields of technology, information and communication. Based on partners' problems, this PKM activity has general objectives, namely, 1) Resolving digital skills issues to improve the soft skills and hard skills of business actors (partners). 2) Resolving partner problems related to product promotion from conventional methods to internet-based methods. 3) Increasing the effectiveness and efficiency of promotions towards fast digital promotion by utilizing social media and websites. 4) Implementation of the adoption of sustainable green economy practices by business actors (partners). The method in this PKM activity goes through 4 core stages, namely 1) partner observation, 2) gradual dissemination of technology, information and communication, 3) intense mentoring consisting of socialization activities, continuous training and mentoring, and 4) activity evaluation. From this training activity, KWT Tuwuh Makmur members were very enthusiastic in participating in each series of activities, namely exploring potential and innovation in online marketing using social media. KWT Tuwuh Makmur has experienced an increase in understanding of digital promotion and is willing to take part in other programs that will be held again because they feel that the services provided can increase knowledge about digital promotion. From the data that has been taken, KWT Tuwuh Makmur hopes that practical training will be learned and applied to make it easier to market products on social media.